Factors Affecting Indonesia's Iron and Steel Exports to Singapore - Febrila, Dinda (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the effect of Singapore's Gross Domestic Product (GDP), Inflation and the Rupiah/US exchange rate on Indonesia's iron and steel exports to Singapore in 2006-2021.This study uses secondary data that is time series. The method used in this study is Ordinary Least Square (OLS) for the multiple linear regression analysis model using the Eviews 10 statistical program.The results of this study indicate that simultaneously GDP, inflation and the exchange rate have a significant effect on the value of Indonesia's iron and steel exports to Singapore in 2006-2021. Partially, Singapore's Gross Domestic Product (GDP) and inflation have had a positive effect on Indonesian iron and steel exports to Singapore in 2006-2021, while the Rupiah exchange rate against the US has a negative effect on Indonesian iron and steel exports to Singapore in 2006-2021.